Exploring a novel GH13_5 α-amylase from Jeotgalibacillus malaysiensis D5T for raw starch hydrolysis - Radzlin, Nurfatini; Mohamad Ali, Mohd Shukuri; Goh, Kian Mau; Yaakop, Amira Suriaty; Zakaria, Iffah Izzati; Kahar, Ummirul Mukminin (Springer Science and Business Media Deutschland GmbH, 2024)
α-Amylase plays a crucial role in the industrial degradation of starch. The genus Jeotgalibacillus of the underexplored marine bacteria family Caryophanaceae has not been investigated in terms of α-amylase production. Herein, we report the comprehensive analysis of an α-amylase (AmyJM) from Jeotgalibacillus malaysiensis D5T (= DSM28777T = KCTC33550T). Protein phylogenetic analysis indicated that AmyJM belongs to glycoside hydrolase family 13 subfamily 5 (GH13_5) and exhibits low sequence identity with known α-amylases, with its closest counterpart being the GH13_5 α-amylase from Bacillus sp. KSM-K38 (51.05% identity). Purified AmyJM (molecular mass of 70 kDa) is stable at a pH range of 5.5–9.0 and optimally active at pH 7.5. The optimum temperature for AmyJM is 40 °C, where the enzyme is reasonably stable at this temperature. Similar to other α-amylases, the presence of CaCl2 enhanced both the activity and stability of AmyJM. AmyJM exhibited activity toward raw and gelatinized forms of starches and related α-glucans, generating a mixture of reducing sugars, such as glucose, maltose, maltotriose, maltotetraose, and maltopentaose. In raw starch hydrolysis, AmyJM exhibited its highest efficiency (51.10% degradation) in hydrolyzing raw wheat starch after 3-h incubation at 40 °C. Under the same conditions, AmyJM also hydrolyzed tapioca, sago, potato, rice, and corn raw starches, yielding 16.01–30.05%. These findings highlight the potential of AmyJM as a biocatalyst for the saccharification of raw starches, particularly those derived from wheat.